A revision of the types of Neotropical Porricondylinae (Diptera: Cecidomyiidae) - Jaschhof, Mathias (Zootaxa, 2014)
The type material of six species of Porricondylinae (Diptera: Cecidomyiidae) described from the Neotropical Region between 1905 and 1936 is re-examined. On the basis of revised adult descriptions the classification of these species is analyzed and discussed. Lectotypes are designated for Asynapta citrinae Felt, A. mangiferae Felt, Holoneurus occidentalis Felt, and Porricondyla gossypii Coquillett.